Human bile microbiota: A retrospective study focusing on age and gender. Issue 2 (February 2021) - Serra, Nicola; Di Carlo, Paola; D'Arpa, Francesco; Battaglia, Emanuele; Fasciana, Teresa; Gulotta, Gaspare; Maida, Carmelo M.; Rodolico, Vito; Giammanco, Anna; Sergi, Consolato
Highlights: This investigation is the first study to evaluate the human bile microbiota with the most extended follow-up using the STROBE guidelines in Italy in a homogenous Italian population. Enterococcus spp. was the most common strain identified in patients with GPB except for patients aged 67−74 years for male (95.2%) and female (80.9%) genders. E. coli and Klebsiella spp. were most frequent than others in every group analyzed. Analogous results were found for bacteria Non-fermenting Gram-negative bacilli (NFGNB), such as Pseudomonas spp. and Stenotrophomonas spp. apart 2nd quartile. Abstract: Aims: The emerging biliary colonization of microorganisms in patients with biliary diseases may be devastating. Recent evidence suggests that age and gender may influence changes in the microbial composition of gut microbiota. To study the relationship between these parameters on bile microbiota, we retrospectively reviewed positive bile cultures following an endoscopic retrograde cholangiopancreatography (ERCP) in a QA-certified academic surgical unit of a single institution. Methods: 449 positive bile cultures from 172 Italian patients with diseases of the biliopancreatic system hospitalized from 2006 through 2017 were investigated for aerobic, anaerobic, and fungal organisms. The patients were stratified into four age intervals (22−66, 67−74, 75−81, and 82−93 years) and followed up for five years. Results: Gram-positive bacteria (GPB) was negatively associated with age only in multivariate analysis (Rpartial = −0.114, p = 0.017), with younger patients prone to harbor GPB and older patients likely to have Gram-negative bacteria (GNB). There was a definite link with the male gender using both univariate and multivariate analysis (p < 0.001). Enterococcus spp. was the most common strain identified in patients with GPB except for patients aged 67−74 years for male (95.2%) and female (80.9%) patients. Escherichia coli and Klebsiella spp. were most frequent than others in every group analyzed. Analogous results were found for bacteria Non-fermenting Gram-negative bacilli (NFGNB), such as Pseudomonas spp. and Stenotrophomonas spp. apart of the 2nd quartile. Conclusions: Our study strengthens the bond of age and gender with bile microbiota composition and suggests that further investigations may be required in targeting the aging microbiome. Other studies should also focus on Mediterranean epidemiological characteristics and antibiotic resistance surveillance system strategies